ANALYSIS OF COSMETICS PRODUCT MARKETING NETWORKS IN INDONESIA ON TIKTOK: A STUDY ON THE TOP 3 BRANDS OF PT PARAGON TECHNOLOGY AND INNOVATION (Jurnal Teknologi Industri Pertanian, 2026)
TikTok has emerged as a primary platform in digital marketing strategies, particularly for beauty products targeting a young and socially active audience. Its strengths lie in the ability to generate viral trends and in its algorithm, which actively promotes content distribution to wider audiences. These features make TikTok an effective medium for fostering engagement among brands, influencers, and consumers. The frequent and intensive interactions among these actors form a promotional network that is not only interconnected but also mutually influential in shaping brand perception, creating symbolic value, and driving purchasing decisions. This study employs social network analysis to explore key actors involved in social media marketing. Using the Social Network Analysis (SNA) approach, the research identifies the structural patterns and relationship dynamics among TikTok users in the context of beauty product marketing. Specifically, the study analyses the digital marketing network of three leading cosmetic products from PT Paragon Technology and Innovation—Wardah, Make Over, and Emina. Data were collected based on engagement rates, number of views, and comment volume. The findings reveal the significant roles and influences of main actors—such as influencers, brands, and consumers—in shaping the digital marketing network. The study highlights that micro-influencers with a high degree of centrality tend to engage more actively in reciprocal interactions and collaborations with other accounts, thereby exerting a stronger promotional influence. It is recommended that future research broaden the scope by comparing digital marketing strategies across different social media platforms to gain a more comprehensive understanding of cross-platform promotional effectiveness. Keywords: influencer, tiktok, network marketing, cosmetics, social network analysis